Circulating Ceramide: A New Cardiometabolic Biomarker in Patients With Comorbid Acute Coronary Syndrome and Type 2 Diabetes Mellitus - Cao, Ruihua; Fang, Zhiyi; Li, Sulei; Xu, Mengqi; Zhang, Jibin; Han, Dong; Hu, Wenchao; Yan, Liqiu; Wang, Yabin; Fan, Li; Cao, Feng (Frontiers in Physiology, 2020)
Aims This study investigated the association of circulating ceramides in patients with comorbid acute coronary syndrome and type 2 diabetes mellitus (ACS-DM). Methods A total of 761 patients with coronary heart disease who were admitted to the Department of Cardiology at the Chinese PLA General Hospital from March to August 2018 were enrolled in this study. Of these 761 patients, 282 were diagnosed with acute coronary syndrome (ACS). We selected 65 patients with ACS-DM (ACS-DM group; mean age 64.88 years; 38 men) and 65 patients with ACS but without any comorbidities (ACS group; mean age 64.68 years; 38 men); the two groups were matched by age and sex. We determined four circulating ceramides in 130 plasma samples: Cer(d18:1/16:0), Cer(d18:1/18:0), Cer(d18:1/24:1), and Cer(d18:1/24:0). The ceramides in plasma samples from patients with ACS and those from patients with ACS-DM were compared. Pearson correlation coefficients between individual ceramides and traditional cardiovascular risk factors for the whole study population were calculated. Multiple logistic regression models were used to evaluate the relativity between the ceramide and ACS-DM. Results Compared with the ACS group, the levels of Cer(d18:1/16:0), Cer(d18:1/18:0), and Cer(d18:1/24:1) and their ratios to Cer(d18:1/24:0) were higher in the ACS-DM group and Cer(d18:1/24:0) was lower in the ACS-DM group (P < 0.05). Correlation analysis demonstrated mild-to-moderate correlations of ceramide and traditional cardiovascular risk factors. There were relatively strong correlations of Cer(d18:1/18:0) and Cer(d18:1/24:1) with C-reactive protein, blood lipids, fasting blood glucose, and glycated hemoglobin A1c. In multiple logistic regression models, Cer(d18:1/18:0) [odds ratio (OR) 2.396; 95% confidence interval (CI) 1.103–5.205; P = 0.027], Cer(d18:1/24:1) (OR 2.826; 95% CI 1.158–6.896; P = 0.023), Cer(d18:1/18:0)/Cer(d18:1/24:0) (OR 2.242; 95% CI 1.103–4.555; P = 0.026), and Cer(d18:1/24:1)/Cer(d18:1/24:0) (OR 2.673; 95% CI 1.225–5.836; P = 0.014) were positively correlated with ACS-DM, and Cer(d18:1/24:0) (OR 0.200; 95% CI 0.051–0.778; P = 0.020) was negatively correlated with ACS-DM. Conclusion Circulating ceramides are positively correlated with the risk of ACS-DM comorbidity. These results give a new insight into the pathogenesis of ACS-DM comorbidity and could provide new options for risk estimation.